Optimizing Preventive Maintenance for DC Battery Back-Up Systems in Gas Turbine Compressors - Gunadi Gunadi; Rosalendro Eddy Nugroho (Journal of Sustainable Economic and Business, 2026)
Objectives: In general, the objective of this Capstone Project is to formulate an optimal preventive maintenance strategy for the DC Battery Backup Control System to support the operational sustainability of Gas Turbine Compressors in the oil and gas sector. Findings: Unit shutdown on July 21, 2024, triggered by a main power supply failure (220 VAC). The battery VRLA (Valve Regulated Lead Acid) type, with a constant load of 10A, the battery should be able to support the load without a 220 Vac power supply for 8 to 10 hours. However, in practice, it can only sustain the load for less than 5 minutes.   Methodology: This study employs a mixed-methods approach, integrating both qualitative and quantitative data. Qualitative data were collected through interviews involving managers, supervisors, and technicians, as well as direct field observations. Quantitative data were obtained from daily operational reports and historical analyzer records. The problem analysis strategy was conducted using a Fishbone Diagram and the 5-Why analysis tool to systematically identify root causes. Conclusion: Based on field observations and technical analysis, battery capacity degradation from its original specification was identified, resulting in the failure of the DC backup battery to sustain the load during the loss of the 220 VAC main power supply. The Fishbone Analysis and 5-Why approach further revealed that human factors played a significant role in contributing to the failure. Based on these findings, corrective actions were implemented, including battery replacement and improvement of the maintenance strategy. Final testing demonstrated a significant improvement in system reliability, with the batteries capable of supporting the control load stably in accordance with operational requirements.